Correlation of Structural, Microstructural, Dielectric, and Impedance Properties in Nd Doping on Bi4Ti2FeO12 Multiferroic Aurivillius Ceramic. Issue 11 (20th September 2022) - Patri, Tirupathi; Durga Rao, T.; Chandra Sekhar, K. S. K. R.; Raghupathi Rao, S.; Rayaprol, S.; Babu, P. D.
Abstract : Bi4− x Nd x FeTi2 O12 (BNFTO, x = 0, 0.5, 1.0, and 1.5) Aurivillius three‐layered ceramics are prepared via a solid‐state reaction method. The crystal structure of the compounds reveals that the compounds exhibit a major orthorhombic structure with the B2cb space group. Slight distortions in the orthorhombic unit cell and an increase in cell volume with the doping of Nd are observed. Highly dense randomly oriented plate‐like nonuniform grains are observed in the micrographs of the ceramics. A decrease in energy bandgap values is noticed in Nd‐doped ceramics from 2.88 to 2.18 eV. An increase in polarization values is observed with Nd doping due to the improved grain boundaries. The appearance of a weak ferromagnetic nature at low temperature followed by a decline in magnetic interaction at room temperature (RT) is observed for all compounds. The frequency and temperature variations of the dielectric constant are investigated. The frequency and temperature variations of the impedance measurements indicate that compounds exhibit non‐Debye‐type electrical relaxations and a negative temperature coefficient of resistance. Furthermore, single‐peak relaxations are predominant for all measured samples, mainly the contribution of intragranular grain regions. This makes Nd‐dopant BNFTO Aurivillius ceramics have a great research value for RT multiferroic applications. Abstract : Structural, microscopic, optical, dielectric, ferroelectric, and magnetic properties of Bi4− x Nd x (Ti2 Fe)O12 ceramics are studied. The evolution of orthorhombic (up to x = 0.5, further monoclinic structure (with dopant x ≥ 1.0), confirms a structural phase transformation. The optical bandgap increases with dopant substitution whereas ferroelectric hysteresis is retained up to x = 1.0. In conclusion, Nd‐substituted Bi4 Ti2 FeO12 exhibits a good multiferroic character.